Tramadol Vs. Meloxicam in Controlling Postoperative Pain in Dental Extractions in Cats - Azin Tavakoli; Parham Pahlavan (Iranian Journal of Veterinary Surgery, 2017)
Objective- Evaluate analgesic effect of meloxicam and tramadol following dental extractions in cats. Design-Experimental study Animals-20 DSH cats who were diagnosed with 3rd or 4th stage of periodontal disease at their third mandibular premolar were entered the study in order to perform surgical dental extraction. Procedure-A blood sample was taken prior to surgery to assess the level of cortisol and CPK. General anesthesia performed using ketamine and diazepam (IV, 8.5 mg/kg+0.2 mg/kg) and inhalation of isoflurane following intubation. 3rd mandibular premolar extracted in all of the patients using surgical procedure. The cats were randomly selected into two groups of A receiving Meloxicam (IV, 0.2 mg/kg) or B, receiving tramadol (IV, 3 mg/kg) at the time of induction of anesthesia. The analgesics were continued after the surgery for 24 hours. The score of pain were recorded using UMPS and assessment of serum level of cortisol and CPK at 2, 4 and 24 hours after the surgery performed. Results-The highest score of pain was recorded at 4 hours after the surgery in both groups. Level of cortisol was significantly higher at 4 hours after the procedure in group B (P= 0.035). The increase in CPK was statistically significant at 2,4 and 24 hours after the surgery in group B when compared to group B (P<0.05). Conclusion and Clinical Relevance- It is concluded that although tramadol and meloxicam are both effective in reducing pain at early hours after the surgery, meloxicam is more effective to control pain after the first few hours.